2019
DOI: 10.1111/and.13479
|View full text |Cite
|
Sign up to set email alerts
|

The effects of verapamil and heparin co‐administration on sperm parameters and oxidative stress in prevention of testicular torsion/detorsion damage in rats

Abstract: In this research, the impacts of combined administration of verapamil and heparin on testicular torsion damage were examined. In this experimental study, 30 sexually mature male Wistar albino rats were divided into five equal groups haphazardly (n = 6): Group 1 was the sham group. In group 2, a 2‐hr testicular torsion was induced, and thereafter, detorsion was done. Rats in group 3 and group 4 experienced an identical surgical procedure like group 2, but verapamil and heparin were administered in 0.3 mg/kg and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 38 publications
1
13
0
Order By: Relevance
“…In our study, CAT values increased in the torsion/detorsion group compared to the control group, but this increase was not statistically significant. Our GSH findings support previous study results (Davoodi et al., 2020; Moradi‐Ozarlou et al., 2020; Sekerci et al., 2017). Chrysin, which we believe has therapeutic power, increased GSH and CAT values in T‐2h/D‐24h + CR group compared to T‐2h/D‐24h group.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In our study, CAT values increased in the torsion/detorsion group compared to the control group, but this increase was not statistically significant. Our GSH findings support previous study results (Davoodi et al., 2020; Moradi‐Ozarlou et al., 2020; Sekerci et al., 2017). Chrysin, which we believe has therapeutic power, increased GSH and CAT values in T‐2h/D‐24h + CR group compared to T‐2h/D‐24h group.…”
Section: Discussionsupporting
confidence: 93%
“…A decrease in catalase and GSH levels has been reported in many of the torsion/detorsion studies (Davoodi, Raisi, Rajabzadeh, Hablolvarid, & Zakian, 2020; Moradi‐Ozarlou et al., 2020; Sekerci et al., 2017). In our study, CAT values increased in the torsion/detorsion group compared to the control group, but this increase was not statistically significant.…”
Section: Discussionmentioning
confidence: 79%
“…In an experiment on the protective effects of Salvia miltiorrhiza extract on renal ischaemia–reperfusion, it was concluded that this herbal remedy could significantly reduce MDA and increase levels of GPx, GSH, CAT and SOD (Chen et al., 2012). In a study conducted by Davoodi, Raisi, et al (2020) regarding the verapamil and heparin co‐administration effects on the prevention of testicular torsion/detorsion injury, it was found that the combination of verapamil and heparin could significantly reduce oxidative stress and detrimental effects of testicular torsion (Davoodi, Raisi, et al, 2020). In our previous research on the effects of Salvia hydroalcoholic extract on testicular TD damage, results indicated that SM administration before detorsion significantly decreased MDA and increased GPx, CAT and TAC levels (Davoodi, Taheri, et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Herein, in the TD group, the level of MDA was increased considerably and levels of GPx, CAT and TAC, decreased. Pretreatment with SMV could noticeably increase the levels of GPx, CAT and TAC (Chen et al., 2012; Davoodi, Raisi, et al, 2020; Davoodi, Taheri, et al, 2020; Sertkaya et al., 2014).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation